The Mapping Multimodal Teaching Materials for Indonesian EFL Students: A Need Analysis - Tandiana, Soni Tantan; Abdullah, Fuad; Andriani, Agis; Hidayati, Arini Nurul; Rosmala, Dewi (Vision: Journal for Language and Foreign Language Learning, 2023)
Multimodality has gained burgeoning attention among scholars from miscellaneous disciplines, such as Linguistics, Discourse Analysis, Semiotics, Sociology, Anthropology, Cultural Studies, and Language Pedagogy. Nevertheless, little is known about the issue of what teaching materials students need to develop their multimodal literacy, notably in the Indonesian EFL milieu. Hence, this case study addresses this void by examining what type of teaching materials university undergraduate students need to cultivate their multimodal literacy. This study involved 99 undergraduate students from three diverse classes as the participants. The data were garnered through a qualitative survey and semi-structured interviews. They were analyzed using thematic analysis (Braun & Clarke, 2006). The findings outlined the needed multimodal teaching materials by the students encompass praxis-oriented multimodal teaching materials, awareness-raising multimodal teaching materials, academic and professional orientation of multimodal teaching materials, simplified and understandable multimodal teaching materials, critical multimodal teaching materials, and visual-verbal relation-informed teaching materials.  The shifting needs of communication, literacy, and 21st-century learning skills remain crucial as a nexus between literacy policies and practices in higher education contexts, especially in Indonesia. More importantly, this study attempts to promote the magnitude of multimodal literacy in language education.